Im schatten des tafelberges - Kleider, Alexander; Michel, Daniela (Germany, 2009)
Cape Town, South Africa: very rarely can poverty and wealth be found as close together as they are in this city. "When the Mountain Meets Its Shadow" tells the story of the Anti-Eviction Campaign, and of Ashraf, Mne, Zoliswa and Arnold, who fight for survival in the informal settlement around Cape Town.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films